Optimal monolithic configuration for heat integrated ethanol steam reformer. (23rd March 2017) - Sidhu, Tejas Puneet Kaur; Govil, Akash; Roy, Shantanu
Abstract: A design concept for optimal design of monolith catalyst is presented through modeling of transport–kinetic interactions in a monolith catalyst. We argue that reactors employing monolithic catalysts should be based on its optimal choice of geometry. In line with that argument, we present a thorough analysis of the geometrical parameters influencing the performance of non-isothermal reactor operation. In this study, an optimal monolith configuration is estimated to be a combination ( d h, t w ) of (0.9 mm, 0.2 mm) for a compact ethanol reformer to produce hydrogen for portable applications where maximum volumetric reactor activity exists. A three-dimensional modeling framework is developed for the resulting optimal monolithic catalyst design that couples the reforming section with a suitable heat source in a recuperative way. As a result, greater ethanol conversion is obtained from the monolith channels near the periphery of the block. The coupling with combustion could predict the formation of cold and hot spots inside the reactor, their nature being dependent on the flow configuration. Further, the effect of altering the feed inlet operating conditions over the variation of ethanol conversion and temperature inside the reactor is also analyzed. The increase in reforming inlet velocity decreases the outlet conversion and shifts the cold spot, forward and deeper in co-flow configuration. The decreasing inlet feed temperature enhances the transfer of heat, eliminating the cold spot. Highlights: Optimal configuration of extruded monolith is based on mass transfer and kinetics, and heat integration. Volumetric reactor activity is optimized by varying hydraulic diameter and wall thickness. Energy intensive coupling of ethanol reforming and combustion is simulated. Temperature distribution in the monolith is obtained, and trends predicted. Movement of temperature excursions is attained with inlet operating conditions.